CA125 in ovarian cancer. (December 2007) - Scholler, Nathalie; Urban, Nicole
A quarter of a century since its discovery, circulating CA125 antigen is recommended for clinical use in the USA for ovarian cancer screening of high-risk women with ovaries, despite its limited sensitivity and specificity. Recent findings suggest that CA125 might also serve as a predictive marker for pre-invasive ovarian carcinoma. Methods to quantify circulating CA125 evolved toward sensitive and reliable double-determinant ELISA assays. The CA125 gene, MUC16, was cloned 20  years after the protein discovery and revealed a very complex and unusual glycoprotein structure, suggesting an immunological role. Recent evidence points toward CA125 function in the induction of materno––fetal tolerance through the alteration of natural killer phenotype. Two receptors for CA125 have been described: mesothelin and galectin-1. The specific location and functional proprieties of CA125 make it a therapeutic target of choice; clinical trials have demonstrated that anti-CA125 injections are well tolerated and suggest a potential survival benefit.